Kwashiorkor caused by a vegan diet. - Hernandez, L.; Hawash, A.; Bellodi Schmidt, F. (European Journal of Pediatric Dermatology, 2024)
Kwashiorkor, a type of severe acute malnutrition, is characterized by decreased or poor-quality protein intake with adequate caloric intake. It is more common in areas with low levels of education, famine, and a limited food supply. This entity rarely occurs in the United States and is associated with avoidance or “fad” diets, extreme poverty, or low nutritional education. A case of kwashiorkor was presented in a 9-month-old American baby who was fed a homemade vegan diet for three months per mother’s preference.